2022
DOI: 10.1371/journal.pone.0263354
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and injury trends in the National Basketball Association: Pre- and per-COVID-19 (2017–2021)

Abstract: Purpose The aim this study was to provide an epidemiological injury analysis of the National Basketball Association, detailing aspects such as frequency rate, characteristics and impact on performance (missed games), including COVID-19 related and non-related injuries. Methods A retrospective study was conducted from the 2017–18 to 2020–2021 season. Publicly available records from the official website of the National Basketball Association were collected, including player’s profiling data, minutes played per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Injury incidence significantly increased in athletes from professional leagues who suffered more injuries after lockdown despite team efforts [ 21 , 34 , 35 ]. This same pattern was observed in our participants, who were based on non-competitive individuals who lacked monitoring from sport science personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Injury incidence significantly increased in athletes from professional leagues who suffered more injuries after lockdown despite team efforts [ 21 , 34 , 35 ]. This same pattern was observed in our participants, who were based on non-competitive individuals who lacked monitoring from sport science personnel.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the rate of injury in NBA players following the COVID-19 pandemic was not significantly higher during the preseason, during the first 4 weeks of the regular season or during playoffs when comparing the 2017–2018 and 2020–2021 NBA seasons ( 36 ). However, when including full seasons, there was an increased incidence of missed matches and injury ratios, from 2017 to 18 until 2020–21, even when excluding COVID-19 related cases ( 37 ). On the other hand, the Qatar 2022 FIFA World Cup is likely to be a challenge for head coaches/managers, strength and conditioning coaches, sport scientists, and medical team members of different clubs.…”
Section: How Injuries Affect Performance and Player Availability In E...mentioning
confidence: 99%
“…9 One study investigating injury incidence during the COVID-19 shortened MLB season demonstrated an increased injury incidence rate compared to the previous season (2020 season: 8.66 per 1000 AEs; 2019 season: 5.13 per 1000 AEs). 3 Previous studies across multiple professional leagues including the National Basketball Association, 10 National Football League, 11,12 European professional soccer leagues, 13 have also reported an increase in injury rates during the 2020 shortened season. However, most of these studies reported comparisons to a single previous season.…”
Section: Introductionmentioning
confidence: 99%